An Analysis of Politeness Strategies Used by the Main Character of “Wonder” Movie : Politeness strategies, Main character, Wonder movie - Julianti, Sinta; Rahmani, Eka Fajar (Kirana Publisher (KNPub), 2024)
The research was examined an analysis of politeness strategies used by the main character of “Wonder” movie. A qualitative descriptive method was employed to analyze the politeness and expressive illocutionary acts depicted in the movie. The data were collected by following Brown and Levinson's strategies, by watching the movie and analyzing its transcript and utterances, focusing on the politeness strategies was the three main characters in that movie. By finding the main character's utterances, the data found 46 positive politeness, 19 negative politeness, 17 bald on record, and 6 off records. The most apparent from the utterance was a positive politeness strategy of asking for a reason. In conclusion, the result is expected to facilitate the English teacher to take the movie as one of the alternative ways to educate skill of good communication. Educators can adopt the politeness strategies as depicted in the “Wonder” movie as same as the other movie in the teaching and learning process in the real classroom.